2018
DOI: 10.1177/0091415017743009
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Career Coaching on Job-Search Behavior of Older Generations

Abstract: This study focuses on career development processes and options for older workers in South Korea and explores how career coaching enhances their career development efforts and transition needs. The purpose of this study is to investigate the structural relationship between older employees' goal-setting, self-efficacy, and job-search behavior mediated by career coaching. A total of 249 participants were recruited in a metropolitan city in South Korea. Based on the literature review, hypotheses were developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…A greater understanding of the relationship between work after retirement and other factors-such as a person's knowledge of the job market and the most effective methods of searching, applying, and interviewing for job openings-is needed. The development of older workers' human capital, including how retirees learn which KSAs need to be acquired or updated in order to match changing labor market demands, is becoming of increasing interest to scholars (Lim, Oh, Ju, & Kim, 2018). Similarly, there is growing interest in studying retirees as the next generation of entrepreneurs (Singh & DeNoble, 2003).…”
Section: Human Capitalmentioning
confidence: 99%
“…A greater understanding of the relationship between work after retirement and other factors-such as a person's knowledge of the job market and the most effective methods of searching, applying, and interviewing for job openings-is needed. The development of older workers' human capital, including how retirees learn which KSAs need to be acquired or updated in order to match changing labor market demands, is becoming of increasing interest to scholars (Lim, Oh, Ju, & Kim, 2018). Similarly, there is growing interest in studying retirees as the next generation of entrepreneurs (Singh & DeNoble, 2003).…”
Section: Human Capitalmentioning
confidence: 99%
“…A similar complex relationship was found between unemployment and psychological well-being [ 20 , 22 ]. The results of unemployment include the loss of income together with a lower standard of living, but also changes in social status, isolation of unemployed people, development of negative self-assessment, changes in self-identity, family disturbance, community relationships, or somatic problems [ 3 , 22 , 23 , 24 , 25 ]. On the other hand, most of the impacts of unemployment have been found in the cognitive domain of well-being (such as status) and they have much less impact on affective well-being and eudaimonic (personal growth and a sense of purpose) well-being [ 22 ].…”
Section: Psychological Well-being and Long-term Unemploymentmentioning
confidence: 99%
“…The promising area of integrating coaching into social work practice lies in professional counseling work with unemployed clients. For coaching in social work with unemployed clients, we can simply use the broad terms “career coaching” or “job coaching” [ 25 , 52 , 53 , 54 ]. Both terms suggest a focus on growth—in career development or job change and/or preservation—and do not invite an impoverishing frame (e.g., dealing with “underlying problems”, “solving unemployment”, “doing treatment”, and “advising by an expert”).…”
Section: Application Of Coaching In Social Work Practicementioning
confidence: 99%
“…For example, Creed et al [ 40 ] found that training significantly increases course participants’ job search self-efficacy. Lim et al [ 41 ] determined that specific interventions, such as promising career coaching programs, facilitate job search behaviors. Cmar and McDonnall [ 42 ] utilized a quasi-experimental pre- and post-test to prove that job search skills training and summer work experience programs could increase participants’ job search self-efficacy.…”
Section: Theories and Hypotheses Developmentmentioning
confidence: 99%